The kappa-opioid agonist U69,593 blocks cocaine-induced enhancement of brain stimulation reward - Tomasiewicz, Hilarie C. (2008)
BACKGROUND: Increasing evidence indicates that brain kappa-opioid receptors (KORs) are involved in regulation of mood states. In animal models often used to study psychiatric illness, KOR agonists produce depressive-like effects (e.g., anhedonia) whereas KOR antagonists produce antidepressant- and anxiolytic-like effects. The ability of KOR agonists to produce anhedonia-like signs in laboratory animals raises the possibility that this class of drugs might be useful to ameliorate states characterized by excess reward or motivation, such as mania or stimulant intoxication. METHODS: We examined how the selective KOR agonist U69,593 affects cocaine-induced facilitation of intracranial self-stimulation (ICSS), a model of the abnormally increased reward function that characterizes mania and stimulant intoxication. Rats with stimulating electrodes implanted in the medial forebrain bundle (MFB) were tested with intraperitoneal injections of U69,593 (0.063–0.5 mg/kg) alone, cocaine (1.25–10 mg/kg) alone, and combinations of the drugs. RESULTS: Cocaine dose-dependently decreased ICSS thresholds, indicating that it enhanced the rewarding impact of MFB stimulation. In contrast, U69,593 dose-dependently increased ICSS thresholds, indicating that it decreased the rewarding impact of the stimulation. Pretreatment with U69,593 blocked cocaine-induced decreases in ICSS thresholds at doses that had negligible effects on their own. CONCLUSIONS: Activation of KORs reduces the reward-related effects of cocaine. Inasmuch as cocaine-induced behavioral stimulation in rodents may model key aspects of enhanced mood in humans, these findings raise the possibility that KOR agonists might ameliorate symptoms of conditions characterized by increased motivation and hyperfunction of brain reward systems, such as mania and stimulant intoxication.